Campaña publicitaria para la prevención del embarazo precoz en las adolescentes de las Unidades Educativas de 8avo a 3er año de bachillerato del cantón Quevedo, año 2015 - Guamán Zamora, Inés Maritza (2015)
Ecuador is in second place among the countries of South America, after of Venezuela in the list of countries high rates of early pregnancies, the most recent census conducted in 2010 were reported 1222.301 pregnant teenagers nationwide a rise of 2.3% per cent yearly, Coast region where focuses the highest percentage of pregnant teenagers with an average of 55.2%, but the Ecuadorian Government state promotes prevention campaigns does not have enough studies to evaluate the capacity to look after the request that hope to be received by provinces and cities that belong to the country. The early pregnancy is a very complex topic that affects the teenagers of the Educational Units of the city Quevedo, for this reason it was taken this social problem in count for perform this research for giving solution to the problem. Through research is was possible to verify that the main difficulty is the lack of information that the teenagers have about topic the early pregnancy, the present research project creates a solution the problem as it is the prevention the early pregnancy designing an advertising campaign targeted exclusively to the teenagers, in the which will be used as media the social network by the easy access that these offer to the young people and the direct advertising like are the posters, triptychs, sheet fliers, promotional material as shirts, caps, pen, cloth bags, pillows, also I am designed a promotional material of recycling by means of the use of plastic bottles for its elaboration. The descriptive and field research, it was used as research instruments a survey with a questions questionnaire, the direct observation and the unstructured interview directed at the teenagers from 8th to 3rd year of baccalaureate of the Educational units of the city of Quevedo, the results obtained primary part for the development the research project. Key words: graphics pieces, promotional material, visual communication, perception visual